Answer:
B is the correct answer of this question
3x + 2y = 12
subtract 3x from both sides
2y = -3x + 12
divide all terms by 2 so that you can have only the y on the left side
y = -3/2x + 6
And that is your answer!
Hope this helped!! :)
Answer:
7/ (3a-1)
Step-by-step explanation:
3a^2 -13a +4 28+7a
------------------ * --------------------
9a^2 -6a+1 a^2 -16
Factor
(3a-1)(a-4) 7(4+a)
------------------ * --------------------
(3a-1) (3a-1) (a-4)(a+4)
Cancel like terms
1 7
------------------ * --------------------
(3a-1) 1
Leaving
7/ (3a-1)
Simplifying
8x + -6 = 7x + 10
Reorder the terms:
-6 + 8x = 7x + 10
Reorder the terms:
-6 + 8x = 10 + 7x
Solving
-6 + 8x = 10 + 7x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-7x' to each side of the equation.
-6 + 8x + -7x = 10 + 7x + -7x
Combine like terms: 8x + -7x = 1x
-6 + 1x = 10 + 7x + -7x
Combine like terms: 7x + -7x = 0
-6 + 1x = 10 + 0
-6 + 1x = 10
Add '6' to each side of the equation.
-6 + 6 + 1x = 10 + 6
Combine like terms: -6 + 6 = 0
0 + 1x = 10 + 6
1x = 10 + 6
Combine like terms: 10 + 6 = 16
1x = 16
Divide each side by '1'.
x = 16
Simplifying
x = 16
HOPE I HELPED!!! :)
Answer:
2
Step-by-step explanation:
Plug 4 in for d and 3 in for c
5d-2/3c
5(4)-2/3(3)
Multiply in the numerator and the denominator
20-2/9
Subtract in the numerator
18/9
2
Hope this helps! :)